THE IMPLEMENTATION OF SNAKE & LADDER BOARD GAME TO IMPROVE STUDENTS’ SPEAKING ABILITY - Kharisma Naidi Warnanda S (Universitas Muhammadiyah Makassar, 2018)
Speaking is a part of language skills which is really essential. Among other skills, speaking is mostly used to communicate with people. The aim of this research was to observe and know the improvement of students’ speaking ability at the second semester students of English Language Education Department, University of Muhammadiyah Malang. There were 24 students under observation. This research employed Classroom second semester students of English Language Education Department, University of Muhammadiyah Malang Action Research (CAR). The researcher implemented two cycles in this research. The first cycle (cycle 1) covered two meetings while cycle two covered three meetings. The test for the students’ speaking performance at cycle 1 showed that the average score of the speaking performance test was 69.92. The standard deviation yielded 4. Meanwhile, the lowest and the highest score were 62 and 78 respectively. At the cycle 2 test, the result showed the average score of the speaking test was 76.50. standard deviation yielded 2. Furthermore, the highest and the lowest score were 80 and 73 respectively. From the cycle 2 result, it proved that the implementation of snake ladder board game could improve the speaking ability of the students at English Language Education Department, University of Muhammadiyah Malang.